INVESTIGATION OF THE EFFECT OF INERTIAL SCRUBBER HYDRAULIC RESISTANCE ON CLEANING EFFICIENCY (Neo Scientific Peer Reviewed Journal, 2025)
The article investigates the effect of inertial scrubber hydraulic resistance on cleaning efficiency of an inertial scrubber that cleans industrial secondary gases in the wet method. In experimental studies, gas velocity, liquid flow and nozzle bore diameter were selected as variable factors. During the examinations, it was found that the intermediate increase in the cleaning efficiency of the minimum and maximum values of liquid consumption was 6.7%, the gas flow rate in the process of hydrogen-fluoride gas cleaning was 17.32 m/s and the cleaning efficiency of the device in a 30% solution of calcium white soda in water was 97.42%.